PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF DENGAN PENDEKATAN LUTHER - SUTOPO DI SMKN 1 UJUNGBATU - Wieke, Erzy Asty; Sri Wahyudi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Advances in digital technology in the field of education call for innovations in learning media that align with the characteristics of Generation Z, who tend to be drawn to visual and interactive digital media. Selecting the right learning methods and media plays a crucial role in supporting the learning process. Based on observations at SMK Negeri 1 Ujungbatu, the Computer Science curriculum still relies on limited learning media, making it necessary to develop more engaging and accessible digital-based learning media. This study aims to develop flipbook-based learning media for the Computer Science subject, specifically on computer hardware material, for 10th-grade students at SMK Negeri 1 Ujungbatu. The method used in this study is the Multimedia Development Life Cycle (MDLC) with the Luther–Sutopo approach, which consists of six stages: concept, design, material collection, assembly, testing, and distribution. The resulting product is a flipbook-based e-module equipped with text, images, instructional videos, practice questions, and simple digital navigation. The media was tested through validation by subject matter experts, media experts, and Computer Science teachers. The validation results showed a percentage of 92.5% from subject matter experts, 87.5% from media experts, and 90% from subject teachers, all categorized as highly valid. Based on the research findings, the flipbook-based learning material developed was found to be highly valid and can be used as a supplementary learning resource for computer science at SMK Negeri 1 Ujungbatu.